2010
DOI: 10.4306/pi.2010.7.4.285
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Association of the Brain-Derived Neurotrophic Factor Gene with Attention-Deficit/Hyperactivity Disorder

Abstract: ObjectiveAttention-deficit/hyperactivity disorder (ADHD) is a complex neurodevelopmental disorder with a strong genetic component. Brain-derived neurotrophic factor (BDNF), which participates in the differentiation and survival of dopaminergic and noradrenergic neurons, could play a role in ADHD development. We aimed to explore the relationships between ADHD and BDNF gene polymorphism.MethodsWe conducted a case-control analysis of 202 ADHD subjects and 159 controls, performed a transmission disequilibrium test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…In the context of BDNF involvement in ADHD, Shim et al (2008) have shown a positive correlation between plasma levels of BDNF and severity of omission errors on a continuous performance test in ADHD children (see also Shim et al 2010). Finally, Cho et al (2010) have reported the association between the BDNF rs11030101 polymorphism and continuous performance errors of commission in a population of ADHD Korean girls.…”
Section: Physical Exercise and Bdnf In Adhdmentioning
confidence: 99%
“…In the context of BDNF involvement in ADHD, Shim et al (2008) have shown a positive correlation between plasma levels of BDNF and severity of omission errors on a continuous performance test in ADHD children (see also Shim et al 2010). Finally, Cho et al (2010) have reported the association between the BDNF rs11030101 polymorphism and continuous performance errors of commission in a population of ADHD Korean girls.…”
Section: Physical Exercise and Bdnf In Adhdmentioning
confidence: 99%
“…Association between DAT1 and ADHD-related traits Jeong et al 123 In the initial analysis, no meaningful association was found between any of the investigated markers and WURS-25 total scores. However, qualitative differences between men and women in the epidemiologic and symptomatic characteristics suggested that we might proceed with further analyses on men and women separately (Biederman et al, 2008;Cho et al, 2010). After this separation, a weak association was found between rs2937639 and WURS-25 total scores in male participants (P = 0.04).…”
Section: Discussionmentioning
confidence: 98%
“…In a study of Korean children, which is the only previous study about the female-specific association between ADHD and BDNF, Cho et al (2010) reported the association between the rs11030101 genetic polymorphism of the BDNF gene and ADHD that was reported first in Korea. However, in this study, the correlation between ADHD and BDNFrs11030101 and rs10835210 genetic polymorphism was found first.…”
Section: Discussionmentioning
confidence: 99%
“…Another case-control (Aureli et al, 2010) association study and a haplotype association analysis (Lanktree et al, 2008) also found that the Val allele was significantly associated with ADHD. However, others could not replicate the results (Friedel et al, 2005;Lee et al, 2007;Schimmelmann et al, 2007;Xu et al, 2007;Ribasés et al, 2008;Cho et al, 2010;Tzang et al, 2013) (Table 1).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation